Dead man's chest : a Phryne Fisher mystery - Greenwood, Kerry (Greenwood, Kerry. Phryne Fisher mystery., 2010)
When she tries to go on summer holiday, Phryne Fisher discovers that the Johnsons, who were supposed to be at the vacation home, are nowhere in sight, beginning a mystery that involves smugglers, pirate treasure, and the mysterious Madame Selavey.